Offshoring Along the Production Chain - Philipp Harms; Oliver Lorz; Dieter Urban (Swiss National Bank, Study Center Gerzensee, 2009)
Recent contributions on offshoring often assume that firms can freely split their production process into separate steps which can be ranked according to the cost savings from producing abroad. We replace this assumption by the notion of a technologically determined sequence of production steps. In our model, cost savings from offshoring fluctuate along the production chain, and moving unfinished goods across borders causes transport costs. We show that, in such a setting, firms may refrain from offshoring even if relocating individual steps would be advantageous in terms of offshoring costs, or they may offshore (almost) the entire production chain to save transport costs. Small variations in model parameters may have a substantial impact on offshoring activities.
Keywords: D24; F10; F23; 330; Offshoring; International Trade; Vertical Production Chain; Auslandsverlagerung; Entscheidung; Betriebliche Wertschöpfung; Vertikale Integration; Außenhandel; Transportkosten; Modularisierung; Unternehmensnetzwerk; Globalisierung; Theorie